Status Nasab Dan Kewarisan Anak Hasil Sewa Rahim Perspektif Majelis Ulama Indonesia Dan Kompilasi Hukum Islam - Nadia Septi Pratiwi; Muhammad Habib (Peduli Riset dan Pengabdian Masyarakat, 2023)
and the inheritance status of children resulting from renting a womb from the perspective of the Indonesian Ulema Council and the Compilation of Islamic Law. This type of research is normative juridical, where this research is studied using library data in the form of books as the source. The method used in this research is a qualitative method, namely more emphasis on aspects of in-depth understanding of a problem. Data analysis was carried out using descriptive analysis and comparative methods. The results of the research explain that based on the fatwa submitted by the Indonesian Ulema Council, it can be concluded that the law of renting a womb (surrogacy) using a womb other than the wife's womb (for example, another woman's womb) is haram, whereas in the Compilation of Islamic Law to date this has not been specifically discussed in detail. regarding womb rental law. The fate of the practice of renting a womb rests with the mother who carries out the birth process. Because children born to surrogate mothers are considered to be children resulting from adulterous relations, the child's hereditary relationship is linked to the mother who gave birth, not to the biological parents. The inheritance status of children resulting from renting a womb is based on the fatwa of the Indonesian Ulema Council and the Compilation of Islamic Law, strengthened by the legislation in force in Indonesia, so it can be concluded that the inheritance status of children resulting from renting a womb is classified as an unrecognized illegitimate child or a child resulting from adultery, if the mother The surrogate has the status of a widow or maiden, because in inheritance law what causes inheritance between the heir and the heir is the existence of a kinship and marriage relationship, while the child born to a surrogate mother does not have a marital relationship